Alfalfa and Forage Kochia Improve Nutritive Value of Semiarid Rangelands. Issue 1 (21st January 2013) - Peel, Michael D.; Waldron, Blair L.; Jensen, Kevin B.; Robins, Joseph G.
Abstract : Obtaining quality forage on semiarid rangeland is challenging. This study compared mid‐summer crude protein (CP) and neutral detergent fiber (NDF) of 'Vavilov' Siberian wheatgrass ( Agropyron fragile ), 'Mustang' Altai wildrye ( Leymus angustus ), two alfalfas ( Medicago sativa ), and two forage kochias ( Kochia prostrata ) in monocultures and binary mixtures at plant densities on 0.25, 0.50, 0.75, and 1.00‐m centers. Crude protein of alfalfa averaged 8.7%, forage kochia 9.6%, Vavilov 4.3%, and Mustang 7.9%. The CP of individual species components within mixtures was similar to their respective monoculture. The CP of forage kochia in both mixtures and monocultures increased 2.1% with increased plant spacing. The CP concentration of the total alfalfa‐grass mixtures averaged 1.2% higher than grass monocultures and 2.5% higher for the forage kochia‐grass mixtures. Forage kochia, alfalfa, and grass NDF concentration averaged 45, 50, and 63%, respectively. The NDF of individual species components was similar regardless of monoculture or mixture and plant density. However, NDF concentration of the total mixture decreased with increasing plant spacing in mixtures that included Vavilov. Under semiarid conditions, CP and NDF concentration of the material tested is influenced more by species composition and less by differences in plant density, or neighboring plants.